Sejam as funções reais f(x) = 3x - 5 e fog(x) = x² - 3.Determine a lei da função de g(x) e determine g(f(2))
Respostas
respondido por:
21
Resposta:
g(x) = (x²+2)/3 e g(f(2)) = 1
Explicação passo-a-passo:
f(x) = 3x-5
f(g(x)) = 3(g(x)) - 5
x² - 3 = 3(g(x)) - 5
x² - 3 + 5 = 3(g(x))
x² + 2 = 3(g(x))
g(x) = (x²+2)/3
===///===
g(f(2)) = ?
f(2) = 3.2-5
f(2) = 6-5
f(2) = 1
g(1) = (1²+2)/3
g(1) = 3/3
g(1) = 1
então g(f(2)) = 1
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás